2021
DOI: 10.1016/j.sjbs.2021.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and biological control of Ralstonia solanacearum from wilt of papaya by natural compounds and Bacillus subtilis: An integrated experimental and computational study

Abstract: Ralstonia solanacearum is a harmful pathogen that causes severe wilt disease in several vegetables. In the present study, we identified R. solanacearum from wilt of papaya by 16S rRNA PCR amplification. Virulence ability of R. solanacearum was determined by amplification of approximately 1500 bp clear band of hrpB gene. Further, in-vitro seed germination assay showed that R. solanacearum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 91 publications
0
8
0
2
Order By: Relevance
“…For the intestinal microbial community, we found that bacterial abundance was altered in the VDR ΔLyz mice compared to controls (Figure 2B). The bacteria Ralstonia solanacearum , a harmful pathogen that causes severe wilt disease in several vegetables, 40 was found significantly upregulated in our VDR ΔLyz mice. Two Lactobacillus species L. johnsonii and L. reuteri , which have been found to enhance gut barrier function and fortify cell protection in pigs, 41 were significantly reduced in our VDR ΔLyz mice (Figure 2C).…”
Section: Resultsmentioning
confidence: 81%
“…For the intestinal microbial community, we found that bacterial abundance was altered in the VDR ΔLyz mice compared to controls (Figure 2B). The bacteria Ralstonia solanacearum , a harmful pathogen that causes severe wilt disease in several vegetables, 40 was found significantly upregulated in our VDR ΔLyz mice. Two Lactobacillus species L. johnsonii and L. reuteri , which have been found to enhance gut barrier function and fortify cell protection in pigs, 41 were significantly reduced in our VDR ΔLyz mice (Figure 2C).…”
Section: Resultsmentioning
confidence: 81%
“…The 16S rDNA was amplified through polymerase chain reaction (Bio-Rad). PCR reaction mixture was prepared (Hossain et al, 2021). The amplification was performed by pre-heating at 95 °C for 5 min.…”
Section: Streaming and Potassium Hydroxide (Koh) Solubility Testmentioning
confidence: 99%
“…The plates were incubated at 28 ± 2°C for 24-48 h. Ten virulent R. solanacearum strains were isolated from infected tomato samples preserved in 10% skim milk kept at -20 °C refrigerator for further studies. For identification of R. solanacearum, gram staining and kovac oxidase tests were conducted (Hossain et al, 2021). Pathogenicity/hypersensitivity reaction test, race and biovar tests were carried out (Popoola et al, 2015) Isolation and identification of R. solanacearum: Diseased tomato stem samples were washed with tap water, and surface sterilized with 70% ethanol for 2 min.…”
mentioning
confidence: 99%
“…Finalmente se incubó durante 24 horas a 37 °C. Para la lectura de resultados, se tomó en cuenta tres partes importantes: primero pico/fondo (si la reacción es ácida será amarilla -A y si la reacción es alcalina será roja -K); segundo la producción de gas (fue leído como positivo o negativo al igual que el tercero), y tercero la producción de ácido sulfhídrico (H 2 S) (Hossain et al, 2021). Esta prueba se realizó por triplicado a cada prueba.…”
Section: Caracterización Morfológica Y Bioquímica De R Solanacearumunclassified
“…La interpretación de los resultados de Kligler hierro agar (Tabla 2) fueron pico de flauta ácido (A) y de fondo de tubo ácido (A); interpretando al ácido cuando existe una coloración amarilla en el medio, lo que significa que el patógeno es fermentador de glucosa y lactosa, a esto se suma la no presencia de un ennegrecimiento, lo que significaría la ausencia de ácido sulfhídrico, esta interpretación se llevó a cabo según la ficha técnica de Rossi (2021). Hossain et al (2021) nos explican que la bacteria tiene diferentes habilidades fermentadoras de azúcares, sumando a sus resultados se logra encontrar algunas investigaciones previas, como las de Barrios Díaz (2015) y Apolinario Carmona (2018), quienes nos indican que R. solanacearum es una bacteria fermentadora de glucosa y lactosa en el medio de Kligler, además de producir una reacción negativa ante la formación de ácido sulfhídrico, ratificando los resultados obtenidos en la presente investigación.…”
Section: Caracterización Morfológica Y Bioquímica De R Solanacearumunclassified